Individual Assistance Programs from FEMA - Regina Fegan; Michael T. Olexa (EDIS)
Most, but not all, federal assistance is in the form of low interest loans to cover expenses not covered by state or local programs, or private insurance. People who do not qualify for loans may be able to apply for a cash grant. This document, IFAS publication DH0432, was published June 1998, revised May 2003. It is part of The Disaster Handbook, a component of the Comprehensive Disaster Preparedness and Recovery Education Module.